Evolution of Balanced Scorecard in the Context of Digital Transformation: A Systematic Literature Review - Rahayu, Mikanti Annisa Sugrining; Heryana, Toni; Widyaningsih, Aristanti (Dinasti Publisher, 2026)
This research investigates the evolution of the Balanced Scorecard (BSC) in the context of digital transformation using a Systematic Literature Review (SLR). Although BSC has been widely applied, existing studies remain fragmented and lack an integrated explanation of how BSC adapts to digital complexity. This study analyzes 31 Scopus-indexed articles published between 2020 and 2025 using the PRISMA approach. The findings reveal three major shifts: (1) BSC has evolved from a static performance measurement tool into a dynamic, data-driven strategic management system supported by AI, big data analytics, and cloud computing; (2) BSC perspectives have developed through either the addition of new dimensions, such as IT environment and sustainability, or the redefinition of the four classical perspectives; and (3) key performance indicators have shifted toward digital-oriented measures, including digital maturity, data security, and sustainability performance. This study contributes by providing an integrated conceptual understanding of the Digital Balanced Scorecard (DBSC) and offers practical insights for organizations in designing adaptive, data-driven performance management systems in the digital era.